Manajemen Pembelajaran Bahasa Jepang pada Peserta Didik Program Magang Jepang di Lembaga Pelatihan Kerja Tomoni Marawa Abadi - Nindya Cahyani; Imam Shofwan (Pusat Riset dan Inovasi Nasional, 2025)
The internship training program in Japan requires participants to have a good command of the Japanese language in order to adapt to so adapt to an international work environment. This study aims to describe the management of Japanese language learning in the internship training program at the Tomoni job training institution. The method used is qualitative descriptive with data collection techniques in the form of interviews, observation, and documentation. The informants in this study included the institution’s leadership, instructors, and trainies. The result of the study indicate that learning management is carried out through three main stages: planning, implementation, and evaluation. During the planning stage, learning objectives are established, and materials, methods, and media are selected based on the needs of the Japanese workplace. The implementation stage focused on practice-based learning with an emphasis on oral and written communication skills. Evaluation is conducted both formatively and summatively to constinuosly measure participants learning outcomes. The conclusion of this study is that learning management at LPK Tomoni is fairly effective, but improvements are still needed, particulary in learning facilities and method variety. Therefore, it is recommended to enhance facilities, provide training for instructors, and continuously adjust the curriculum.